HUBUNGAN KOMUNIKASI INTERPERSONAL DENGAN PERILAKU BULLYING PADA SISWA KELAS IX SMP SWASTA KARYA JAYA TANJUNG MORAWA TAHUN AJARAN 2021/2022 - Zita Fakhrani Idzni; Nurul Azmi Saragih (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the relationship between interpersonal communication and bullying behavior in students in class IX of Karya Jaya Private Junior High School Tanjung Morawa. The hypothesis proposed is that there is a positive and significant relationship between interpersonal communication and bullying behavior in grade IX students at Karya Jaya Private Junior High School Tanjung Morawa. The research method used is descriptive quantitative approach with the type of research used is descriptive correlational research. Determination of the sample of this study was a population study of 86. The sample in this study was 40 people to obtain the necessary data, so in this study the researchers used data collection tools in the form of questionnaires and documentation. Furthermore, the results of research at the Karya Jaya Tanjung Morawa Private Junior High School used product moment correlation calculations. The two variables are bullying behavior (X) and interpersonal communication (Y). The level of bullying behavior of students is 68.12% in the high category, the level of interpersonal communication is 63.12% in the high category, the level of interpersonal communication with bullying behavior is r_count 0.269> r_table 0.331. This shows that there is a relationship between interpersonal communication and bullying behavior in students. Based on the discussion and data analysis, it can be concluded that the hypothesis which states